2009
DOI: 10.1002/ibd.20660
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Dendritic Cells and Epithelial Barrier Dysfunction in Crohnʼs Disease

Abstract: Crohn's disease (CD) is a chronic gastrointestinal inflammatory disorder considered to be the result of an inappropriate and exaggerated mucosal immune reaction to yet undefined triggers from the gut flora in genetically predisposed individuals. This inflammatory phenomenon has been characterized by an adaptive T-cell response in addition to an abnormal function of the innate immune system. Dendritic cells (DCs) are constituents of this innate system, inducing T-cell activation via antigen presentation. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 185 publications
(160 reference statements)
0
33
0
Order By: Relevance
“…28 In the PB of patients with IBD, increased numbers of DC expressing CD83 and CD86 have been found and matured DC generated from peripheral blood monocytes of IBD patients show raised immune-stimulating abilities when compared with those of healthy volunteers. 39 Activated DC found at the sites of inflammation in murine models of colitis might contribute to the pathogenesis, 11 and there is increasing evidence that mucosal DC accumulated within inflamed tissue might also play a role in human IBD. 16,40 Regarding DC in the peripheral blood of IBD patients, conflicting results have been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 In the PB of patients with IBD, increased numbers of DC expressing CD83 and CD86 have been found and matured DC generated from peripheral blood monocytes of IBD patients show raised immune-stimulating abilities when compared with those of healthy volunteers. 39 Activated DC found at the sites of inflammation in murine models of colitis might contribute to the pathogenesis, 11 and there is increasing evidence that mucosal DC accumulated within inflamed tissue might also play a role in human IBD. 16,40 Regarding DC in the peripheral blood of IBD patients, conflicting results have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…8 Mucosal pDC and mDC have been investigated in only a few human studies, although accumulation of activated DC at the sites of inflammation may contribute to the pathogenesis of human inflammatory bowel disease (IBD). 6,[9][10][11][12] Reduced proportions of immature pDC have been found in the peripheral blood (PB) of patients with IBD, suggesting their recruitment to inflamed mucosal tissues. 13,14 Additionally, mesenteric lymph node (MLN) pDC express the chemokine receptor CCR6, which could explain musosal accumulation at inflamed tissue sites as a consequence of up-regulated mucosal addressines such as CCL20 or mucosal addressin cell adhesion molecule-1.…”
Section: M U N O L O G Y O R I G I N a L A R T I C L Ementioning
confidence: 99%
“…Components of the intestinal barrier are likely to play a more active role: an in vitro study has demonstrated the potential for cross-talk with, or recruitment of, inflammatory cells, particularly by dendritic cells [49,58]. Their role as antigen-presenting cells capable of influencing T-cell responses makes dendritic cell function in CD an intriguing avenue of study.…”
Section: Other Factors Influencing Bacterial Clearance Intestinal Barmentioning
confidence: 99%
“…In health, a polarized monolayer of columnar intestinal epithelial cells normally forms a tight barrier to the access of toxic agents to the mucosal immune system (11). However, IFN-␥ disrupts tight junctions and thereby disturbs paracellular transport mechanisms.…”
mentioning
confidence: 99%